Evaluation of the Management Policy of BOS Funds in Elementary Schools - Nurisnain, Mahdarizky Muhammad; Mursyidah, Lailul (Indonesian Journal of Law and Economics Review, 2024)
General background however, the effective management of these funds remains a significant challenge, particularly in certain regions. Specific background this study focuses on evaluating the management policy of BOS funds at an elementary school, highlighting the need for systematic assessment criteria that align with established standards. Knowledge gap despite the existence of frameworks for evaluating fund management, there is limited research on their practical application in specific educational contexts. The aim is to analyze the BOS fund management by employing evaluation indicators based on Wirawan's framework, which includes input, process, output, and impact assessments. The results reveal that while the school’s facilities and infrastructure are generally in good condition, delays in fund distribution have adversely affected maintenance efforts. Key factors influencing successful fund management include meticulous planning, effective coordination, and accurate reporting. Furthermore, the study finds that BOS funds significantly reduce operational costs, benefiting both educators and students. Novelty this research contributes novel insights into the evaluation process of educational funding, illustrating how structured assessments can improve management practices. The implications of this study suggest that better fund management can lead to enhanced educational outcomes and resource allocation, ultimately fostering an environment conducive to learning. Highlights: Evaluation of BOS fund management enhances accountability and resource allocation. Delays in fund distribution impact maintenance of school facilities. Structured assessments improve educational outcomes and support effective learning environments. Keywords: BOS , Educational Management, Evaluation, Operational Costs, Infrastructure